Ocular Surface Infection and Antimicrobials - Willcox, Mark; Stapleton, Fiona; Dutta, Debarun (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint collates papers from a Special Issue of the journal Antibiotics, which was entitled "Ocular surface Infection and Antimicrobials". The papers cover aspects such as common microbes which cause ocular infections and their susceptibility to antibiotics; how guidelines for antibiotic use can translate to improved patient compliance; how bacteria respond to antibiotics; and lastly, new treatments and ways of preventing ocular surface infections.